Pemanfaatan Strategi Promosi terhadap Minat Beli Followers Instagram @paktani.co pada Produk Sayur Pack - Serrina Dwi Handini; Fadli Mulyadi; Vi’in Ayu Pertiwi (Jurnal Sosial Ekonomi Pertanian, 2023)
The presence of social media is considered to facilitate users in buying and selling products. However, not all marketers have a strategy for marketing their products on social media. This research was conducted to explore the influence of social media promotion strategies carried out by the @paktani.co instagram account because it is considered less extensive in marketing its products. Therefore, it is necessary to further investigate the effect of promotional strategies carried out by the @paktani.co instagram account to determine the purchase intention of the products offered. This research was conducted from October to December 2022, with 100 respondents determined through judgment sampling and analyzed using multiple linear regression analysis. The result of this study is that the level of interest in buying vegetable packs on the @paktani.co Instagram account is at a medium level and already at the stage of desire to buy the product. There is a positive and significant influence on the context and connection variables on the interest in buying vegetable packs partially. Meanwhile, all independent variables, namely context, communication, collaboration, and connection, have a positive and significant effect together with a contribution of 57.1% to the purchase intention of packaged vegetables on the @paktani.co Instagram account.